Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702411
|View full text |Cite
|
Sign up to set email alerts
|

The Known Stranger

Abstract: Striking up a good conversation with new acquaintances is often difficult. In this paper we introduce a system that uses a ranking recommendation algorithm to generate real-time personalized topic suggestions during a conversation. The system then delivers the suggestions via Google Glass. We conducted a study with 38 pairs of strangers, who received such suggestions while conversing with a person they met for the first time. Participants found the suggestions to be helpful, but only at the right moments, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Prior research had revealed that extroverts share more information in their profiles when augmenting conversations in face-to-face meetings [30]. However, similar to work on topic suggestions in conversations [39], our study hints towards the use of such information was less valuable to extroverts, as they do not need such support in conversations. Therefore, we see one opportunity in designing for supporting introverts in managing their social interactions.…”
Section: Individual Strategies For Collocated Personal Sharingsupporting
confidence: 51%
See 2 more Smart Citations
“…Prior research had revealed that extroverts share more information in their profiles when augmenting conversations in face-to-face meetings [30]. However, similar to work on topic suggestions in conversations [39], our study hints towards the use of such information was less valuable to extroverts, as they do not need such support in conversations. Therefore, we see one opportunity in designing for supporting introverts in managing their social interactions.…”
Section: Individual Strategies For Collocated Personal Sharingsupporting
confidence: 51%
“…Most design objectives for supporting face-to-face interactions, like increasing awareness or breaking ice in new encounters [40] have focused on design approaches with discrete interactions (e.g. topic suggestions [39]). As self-expression serves more than as a means to translate to more discrete interactions [14], a promising approach would be to design new forms of augmenting self-expression.…”
Section: Willingness To Share a Personal Representations In Publicmentioning
confidence: 99%
See 1 more Smart Citation
“…nurse, taxi driver), so building commonality earlier is better. Recent work has continued to explore this concept of computer-supported icebreaking (Nguyen, Nguyen, Iqbal, & Ofek, 2015), though not necessarily using location history.…”
Section: Lifelogging and Identity Interfaces: Evaluating Applicationsmentioning
confidence: 99%
“…Whilst this affordance of sharing a screen does not exist in the case of head-mounted display devices, they provide 'heads-up' interaction and can deliver information close to the line of sight [31,46]. They hence are unlike smartwatches and smartphones, which are elsewhere, such as on the wrist, in a pocket, or held in our hands.…”
Section: Introductionmentioning
confidence: 99%